Pendampingan Pembuatan Nomor Induk Berusaha dan Sertifikasi Halal bagi Para Pelaku Usaha UMKM di Kecamatan Singaran Pati - Wardi, Alka Inka Kusuma; Isnaini, Desi; Hasanah, Uswatun (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
Micro, Small, and Medium Enterprises or MSMEs are an important part of the economy of a region or country. By developing MSMEs it can provide its own meaning in increasing the value of a country's economic growth and can reduce the value of poverty in a country. The existence of Micro, Small and Medium Enterprises (MSMEs) can be the backbone of a country's economy, because their form of business can revive a declining economy. According to Law Number 20 of 2008 concerning Micro, Small and Medium Enterprises, MSMEs have a very vital role in development and economic growth, but only in developing countries such as Indonesia, but also in developed countries. The main objective of this assistance is to increase the number of MSMEs that obtain NIB and Halal Certification, strengthen consumer confidence, provide guarantees in the production process for producers, increase product competitiveness, stimulate sales turnover growth, open up global marketing opportunities, and comply with government regulations regarding legality. halal business and regulations. The implementation of this mentoring program consists of three stages, namely: pre-service, implementation of mentoring and post-mentoring evaluation. Mentoring activities involve several aspects, such as providing an understanding of the importance of NIB and Halal Certification for MSMEs, assisting in managing business legality through Business Identification Numbers (NIB) and facilitating halal certification programs, and the halal logo is part of this mentoring effort. This activity is focused on MSMEs located in Singaran Pati District, Bengkulu City. Assistance was carried out between 30 May and 30 September 2024, involving 10 business actors. Through the outreach of NIB, SIINas and halal certification. As of the end of September, 3 halal certifications had been issued by the MUI based on the results of assistance and 7 were still in the process of applying for halal certification.